Bases legais para a atuação da fisioterapia do trabalho no Brasil: um estudo qualitativo documental - Duque, Nathália Gongora (Universidade Federal de São Carlos, 2025)
Occupational Physiotherapy has been a specialty of Physiotherapy since 2008 in Brazil. However, there are major challenges for the social recognition of this Physiotherapy specialty. The aim of this study was to systematize the legal basis about the role of Occupational Physiotherapists in Brazil and to build a timeline with the documentary landmarks of this Physiotherapy specialty. This documentary study was carried out by searches in SciELO, Pubmed/Medline and Google Scholar databases. Data analysis was carried out through descriptive analysis. Eighteen (18) scientific articles published between 2008 and 2023 were included. The legal basis for occupational physiotherapists is mainly based on the resolutions of the federal councils, regulatory standards, laws and ordinances of the Ministries of Health and Labor and Employment. The timeline revealed the importance of associations and academic and clinical professionals in defining the role of Occupational Physiotherapy. The legal documents demonstrated the evolution of Occupational Physiotherapy specialty and the strengthening of the area through the actions of associations, class councils and professionals.
Legal basis for the practice of occupational physiotherapy in Brazil: a qualitative documentary study
Keywords: Especialidade de fisioterapia; Saúde ocupacional; Ergonomia; Legislação; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL